Molecular structure of cyclomaltodextrinase derived from amylolytic lactic acid bacterium Enterococcus faecium K-1 and properties of recombinant enzymes expressed in Escherichia coli and Lactobacillus plantarum - Kridsada Unban (2018)
© 2017 Elsevier B.V. Gene encoding cyclomaltodextrinase (Cdx) from amylolytic lactic acid bacterium Enterococcus faecium K-1 was cloned and nucleotide sequence was analyzed. The open-reading frame consisted of 1767 bp encoding 588 deduced amino acids. Consequently, four typically conserved regions of the glycoside hydrolase family 13 were revealed; however, nine exceeding amino acids (DSYQMTDVP) were found at the 282–290 position in comparison to previously reported cyclomaltodextrinases. This difference is believed to have an influence on the substrate specificity of this enzyme. The recombinant CDases expressed in Escherichia coli BL21 (CDX_E) and Lactobacillus plantarum WCFS1 (CDX_L) with high expression levels of 8041 and 5511 U/L were purified by Ni-NTA affinity chromatography. The active form CDX is a dimeric protein with two identical subunits of 62 kDa, approximately. Both CDX_E and CDX_L revealed nearly similar properties, but the thermostability of CDX_L was slightly higher. Mn 2+ and Co 2+ at a concentration of 1 mM stimulated the enzyme activity, while the Ag + , Cu 2+ and SDS solution completely inhibited enzyme activity. CDX exhibited the highest activity with α-cyclodextrin and β-cyclodextrin, but lower toward pullulan and starch. Importantly, this is the first report describing genes, the molecular structure and properties of cyclomaltodextrinase derived from lactic acid bacteria E. faecium.